Can saliva testing replace blood measurements for health monitoring? Insights from a correlation study of salivary and whole blood glutathione in humans. Issue 15 (9th June 2016) - Ngamchuea, Kamonwad; Batchelor-McAuley, Christopher; Cowen, Philip J.; Williams, Clare; Gonçalves, Luís Moreira; Compton, Richard G.
Abstract : The feasibility of using saliva samples as diagnostic for health status is assessed. Abstract : The feasibility of using saliva samples as diagnostic for health status is assessed. Although blood is regularly used for this purpose, an alternative non-invasive route which yields equivalent clinical information is desirable. The non-invasive saliva testing is validated by comparing its result to that of blood examination. In this investigation, we used glutathione as a paradigmatic example of a biomarker and diagnostic auxiliary. Correlation between the levels of total unbound glutathione, reduced and oxidized, in saliva and whole blood samples from healthy individuals is evaluated. Both salivary and blood glutathione were measured using an enzymatic kinetic assay which was improved to eliminate measurement errors arising from the variation in the enzyme activity from different batches.